Non-random Plaque-site Recurrence of Psoriasis in Patients Treated with Dead Sea Climatotherapy - Thomas Emmanuel; Dorte Lybaek; Claus Johansen; Lars Iversen (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)